Should gender equiality be imposed in section 375 penal code? - Sarwitaa Pushparajah,; Nur Sofea Agustiar,; Nur Azlina Azizan,; Walnvika Poon Nam, (Penerbit Universiti Kebangsaan Malaysia, 2023)
One of the most horrifying tools of terror employed against women is sexual violence. However, a significant portion of victims are men. Numerous studies have found that women are sexually abused more frequently than gender stereotypes would imply. The law only recognises ”the penetration of the vagina by a man” as the necessary ingredient to establish that rape or sexual activity occurred, hence a man cannot be legally raped by a woman. The claim that only women can be victims of rape because only men can penetrate the vagina. Nevertheless, rape affects both men and women equally. Several stereotypes make it challenging for a man to publicly disclose a history of rape or sexual assault. These downplay the severity of the crime and discourage males from asking for help. The purpose of this article is to do research on the impact of the rape provision in cases of male rape and to determine whether the stated provision should promote gender equality. The method employed in this article is qualitatively based. The article finds that rape is a gender specified crime. The provision for rape mainly only classifies for women but not men. Therefore, the provision of Section 375 should be improved and amended as it is possible for a woman to rape a man. Speaking of rape, it is still illegal whether it is committed against a man or a woman.